Effect Of Crumb Rubber Incorporation On The Behaviour Of Concrete Beam Subjected To Impact Load - Altayeb, Mustafa M. M. (2013)
It is well known that concrete containing crumb rubber would enhance the elastic properties of concrete as well as ability to absorb energy. However, the actual flexural energy under impact load is still questionable and debatable. Moreover, the behavior of hybrid (rubberized top-plain bottom) concrete structures under impact or static load conditions are yet to be investigated. In this study, experimental and nonlinear dynamic analysis of rubberized concrete under impact load was investigated. Rubberized concrete samples were prepared by partial substitution (5%, 10% and 20 % replacements by volume) of sand or cement by two size of crumb or powder rubber respectively, and tested under impact three-point bending load, as well as static load. Three types of specimens namely, plain concrete, rubberized concrete, and double layer concrete were loaded to failure in a drop-weight impact machine by subjecting to 20N weight from a height of 300mm, and another three similar specimens were used for the static load test. In both tests, the load-deflection and fracture energy of each specimen were investigated. Finite-element simulations were also performed to study the dynamic behaviours of the samples, by using LUSAS V.14 software. The concrete beam was modeled to be built with eight node hexahedron elements and elasto-plastic material was used to model both plain and rubberized concrete structures. Explicit nonlinear dynamic scheme was used to determine the deflection increments for each time step.In general the result was noticed that, the impact loads increased with the increase in the percentage of rubber.